FACTORS INFLUENCING ACADEMIC FRAUD BEHAVIOR AMONG UNIVERSITY STUDENTS DURING THE COVID-19 PANDEMIC: A LITERATURE REVIEW - Kumalasari, Sunnia; Firmanto Adi Nurcahyo (Jurnal Tunas Pendidikan, 2025)
he Covid-19 pandemic has changed how we learn, moving from in-person classes to online education. However, the implementation of online comes with challenges, especially the rise of fraud academic. This study uses a method called literature review by analyzing at 10 selected scholarly articles to understand the factors affecting fraud academic during online learning. This literature finds two main types of factors. Positive factors, such as capability, misuse of technology, and low religiosity, are identified as triggers student to cheat. On the other hand, negative factors like ego do not influence the tendency toward academic fraud. The study also shows that different researchers have different views on what makes students cheat, such as rationalization, opportunity, and pressured. The anticipated outcomes of this research are aimed at furnishing a comprehensive comprehension and facilitating the resolution of issues related to academic dishonesty within the context of online learning.